Factors Influencing The Six-Month Mortality Rate In Patients With A Hip Fracture - Prodovic Tanja; Ristic Branko; Rancic Nemanja; Bukumiric Zoran; Zeljko Stepanovic; Ignjatovic-Ristic Dragana (Slovenian Journal of Public Health, 2016)
There are several potential risk factors in patients with a hip fracture for a higher rate of mortality that include: comorbid disorders, poor general health, age, male gender, poor mobility prior to injury, type of fracture, poor cognitive status, place of residence. The aim of this study was to assess the influence of potential risk factors for six-month mortality in hip fracture patients.